Patients’ suggestions for improvements to text-based e-consultations. An online survey of users of the national health portal in Norway - Eli Kristiansen; Eli Kristiansen; Helen Atherton; Trine Strand Bergmo; Paolo Zanaboni (Frontiers in Digital Health)
BackgroundIn recent years, text-based e-consultations have been widely implemented in general practice and are appreciated by patients for their convenience and efficiency. Policymakers aim to enhance patient access to clinical services with the general practitioner (GP) through text-based e-consultations. However, concerns are raised about their efficiency and security. We aimed to investigate users’ perceptions of potential improvements in the text-based e-consultation service provided by the national health portal in Norway.MethodWe conducted an online survey among users of text-based e-consultations with the GP on the national health portal Helsenorge. The survey was available from January-February 2023 and consisted of 20 questions. This study focused on the free-text answers to the question “Do you have any suggestions to improve the service?” The framework method was used for a thematic analysis of the answers.ResultsThe analysis of 2,954 free-text answers from users of the national e-consultation service resulted in six areas where suggestions for improvement were expressed. According to users, the service would benefit from: (1) a better set-up to facilitate the formulation of the patient's problem, (2) better value for money (in regards to both price and quality), (3) faster response time, (4) improved information and predictability about the status of the e-consultation (e.g., if it is received and when to expect an answer), (5) improvement in technical issues, and (6) improvement of access to dialogue-based services to replace or complement e-consultations.ConclusionThe analysis of users’ suggestions for improvements to the e-consultation service emphasised the need to customise the service to address individual patient needs. Users found a one-size-fits-all approach with mandatory questions, fixed pricing, and inflexible response times less appreciated. Some also felt forced to rely on e-consultations due to the perceived poor availability of other GP services. This highlights the importance of perceiving e-consultations not as a replacement for dialogue-enabled services, but rather as a potentially efficient addition, ensuring a well-tailored setup for appropriate patient use.